MANAGEMENT ACCOUNTING PRACTICES ADOPTION AND DETERMINANTS: A REVIEW OF WORLDWIDE EMPIRICAL EVIDENCES - Jariya, A.M.I.; Velnampy, T. (University of Jaffna, 2021)
There is a common belief that the management accounting practices adoption offers relevant and timely information to mangers for making economic decisions and thereby improving an organization's performance. However, there are notable differences in the adoption of different MAPs, its extent, and determinants across different nations. Directed by this fact, the search for knowledge of the context that determines the adoption of MAPs is growing. To explore the intuition in understanding the MAPs’ adoption across different countries worldwide, the objectives of this article are to review the prior empirical literature on the level of adoption and benefits of adopting MAPs, to identify the factors which determine MAPs’ adoption across different countries, and to develop a conceptual framework that could be used for future research. There are forty-three research articles reviewed both from developed and developing countries, including evidence from the USA, UK, Europe, Japan, Australia, New Zealand, Taiwan, Malaysia, Singapore, China, Finland, Turkey, Vietnam, Barbados, Jamaica, Egypt, Libya, Iran, Bali, India, Estonia, Canada, Thailand, Jordan, Tehran, Kenya, Tunisian,the Czech Republic and Nigeria. The review reveals that the adoption of MAPs significantly differs across countries; the adoption of traditional MAPs is widely available worldwide, and the adoption of advanced MAPs such as activity-based costing and balanced scorecards is higher in developed countries. Further, the review identified national culture, size, competition, perceived environmental uncertainty, advanced manufacturing technology, organizational structure, organizational strategy, customer power, total quality management, the complexity of processing system, product perishable, organizational capacity to learn, industry type, the origin of organization, owner-manager commitment, Life cycle stage of the firm, interactive use, diagnostic use, dynamic tension, organizational DNA, rational capital with the supplier and interactive control as the determinants of MAPs. However, the review reports that these factors have mixed evidence concerning MAPs’ adoption. Finally, a conceptual framework has been developed based on the contingency theory of management accounting related to the determinants of MAPs that could be empirically tested for future research.
Keywords: Management accounting practices; Adoption; Benefits; Determinants; Empirical review